Akselerasi Literasi Zakat Produktif sebagai Upaya Pembangunan Ekonomi Masyarakat Kecamatan Muara Telang Kabupaten Banyuasin - Pamuji Pamuji (Forum Kerjasama Pendidikan Tinggi, 2023)
The potential of zakat with the reality of zakat has really happened, one of the problems is the acceleration of zakat literacy which is low in public understanding. This study attempts to examine the level of zakat literacy in the scope of the community, namely in Muara Telang District, Banyuasin Regency. The focus of this research is the level of people's basic understanding of the obligation to pay zakat. In this study used qualitative methods. Data collection techniques used are interviews, observation and documentation. This effort was made to explore phenomena in society as sources of data objectively in the field. The steps to collect, select, and transform data into information are then analyzed using a descriptive approach to provide an overview of the efforts that have been made for economic development. The results of this study indicate that the community understands the basic knowledge of zakat quite well, although a researcher and evidence of productive zakat are needed as an effort to improve zakat literacy even better.